Technostress: Mediating Accounting Information System Performance - Saganuwan, M. U.; ., U. N. U. Ahmad (Information Management and Business Review, 2013)
In recent times, Accounting Information System (AIS) characteristics were studied to enhance its effectiveness but the impact technology stress, which imposes additional stress in the professionals known as techno stress, is not reflected. Technostress and AIS literatures were reviewed to synthesize the relationship. Technostress adversely affect the professional’s job satisfaction and performance. Therefore, this conceptual paper highlights and synthesizes the issues of techno stress with professionals and the effectiveness of AIS in organizations. However, based on the strength of existing frameworks of AIS, techno stress use to mediate the technological, organizational and cognitive contingency factors under condition of uncertainty to determine AIS effectiveness.